NANOEMULSIFIKASI SPONTAN EKSTRAK JINTAN HITAM DAN KARAKTERISTIK PRODUK ENKAPSULASINYA [Spontaneous Nanoemulsification of Black Cumin Extract and the Characteristics of Encapsulation Product] - Rovie Farah Diba; Sedarnawati Yasni; Sri Yuliani (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
Low energy nano technology research with black cumin materials is still limited. Encapsulation of black cumin extract nanoemulsion has been developed and the products have been characterized. The aims of this study are determining the extraction method of black cumin seed, formulating black cumin extract nanoemulsion by spontaneous emulsification technique, and encapsulating black cumin extract nanoemulsion. Three stages of experiments were done in this study, i.e. extraction, nanoemulsification and encapsulation. First, extraction was done using maceration and reflux method and the best result was sent to the nanoemulsification process. Second, a spontaneous nanoemulsification was performed involving organic phase (black cumin extracts were dissolved in ethanol 70%), and water phase (Tween 80 solution with three different percentages 1, 2 and 3% w/w) to produced the best nanoemulsion. Third, the best nanoemulsion based on size, homogeneity, and stability of the particles, was encapsulated using two different encapsulating material compositions, i.e. maltodextrin (100%) and combination of maltodextrin and soy protein isolate at a ratio 80 and 20 (w/w). The results showed that three-hour reflux method produced better black cumin extract properties than that of maceration method. A percentage of 3% surfactant gave a stable nanoemulsion with average droplet size of 10.93 nm. Reconstitution of nanoemulsion encapsulation product that has more spherical globules, indicated efficient encapsulation process. The use of combination of maltodextrin and soy protein isolate provided a better preservation of phenolic content and antioxidant capacity as compared to the use of maltodextrin alone.